(untitled) (Olhar de Professor, 2024)
The article proposes to reflect on some important concepts in the field of Literacy considered from its constitution over 40 years from a discursive-dialogical perspective. Starting from a metaphorical bias, the authors seek to construct such reflection focusing on teaching relationships, the constitution of authorship and the relationship between teachers and children in the constitution of texts with meanings and meanings, elaborated from the awakening of authorial consciousness as a way in which These subjects can carry out authentic readings of the world using the language that constitutes their writing and inscription in the world, based on relationships with Others through the lens of Historical-Cultural Psychology. The results indicate that through teaching relationships, possibilities arise for the mobilization of desires and the ability of children to relate and position themselves in the world and with/about their own productions.